Identifikasi Zat Pewarna Rhodamin B pada Sampel Makanan Menggunakan Metode Rapid Test di Loka POM di Kota Surakarta - Prastiwi, Salma Maulidya (Jurnal Teknologi dan Industri Pertanian Indonesia, 2024)
There are many problems regarding cases of misuse of hazardous substances in food carried out by business actors by adding Rhodamine B dye. Therefore, the Government, in this case, BPOM and its staff, namely BBPOM/BPOM/Loka POM, routinely supervise and secure, including sampling samples suspected of containing hazardous materials. In carrying out its duties of supervising processed food, the POM Workshop in Surakarta City in its supervision area, the POM Workshop in Surakarta City conducts cross-sectoral guidance to business actors not to resell products that positively contain Rhodamin B. The purpose of carrying out practical work is to find out the Rhodamin B dye test on samples obtained from traditional markets in Surakarta City, Central Java. The sample testing method was carried out using the Rhodamin B Rapid Test. Nine samples were tested: rengginang crackers, cleret crackers, gado-gado crackers, chili powder, cenil, kueku, sentiling, chili sauce, and tomato sauce. The results of the Rhodamin B test on nine samples showed that two of the samples tested were suspected of containing Rhodamin B dye. So it can be concluded that there are still foods on the market using Rhodamin B dye.